To simplify the square root of 60, we can factor 60 into its prime factors:
\[ 60 = 2^2 \times 3 \times 5 \]
Now, we can express the square root as follows:
\[ \sqrt{60} = \sqrt{2^2 \times 3 \times 5} \]
Using the property of square roots that states \(\sqrt{a \times b} = \sqrt{a} \times \sqrt{b}\), we can separate the perfect square:
\[ \sqrt{60} = \sqrt{2^2} \times \sqrt{3 \times 5} \]
Calculating the square root of \(2^2\):
\[ \sqrt{60} = 2 \times \sqrt{15} \]
Thus, the simplified form of \(\sqrt{60}\) is:
\[ \boxed{2\sqrt{15}} \]